1970
DOI: 10.1029/jc075i036p07573
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory investigations of temporary collisions of raindrops

Abstract: The collision of drops with diameters ranging from 2.0 to 4.5 mm was studied with the velocity differences of the drop pairs equal to those observed in nature. Breakup normally occurred and produced 4.2 fragments on the average. The original two droplets reappear as the larger fragments with very little change in size, and the smaller fragments were formed by the disruption of a joining neck. The collision and breakup are, therefore, basically temporary coalescence. Changes in surface tension did not affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Measurements for ∆ > 1 by List, MacNeil & McTaggart-Cowan (1970), McTaggart-Cowan & List (1975, and Bradley & Stow (1979) for water drops and by Arkhipov et al (1983) for water glycerine solutions, showed that, as in our case (e.g. compare figure 7e-h with figure 6 of List et al (1970) and figure 1 of Bradley & Stow 1979), the fragmentation of size-asymmetric systems is characterized by a three-peaked residue-mass distribution, two of the groups corresponding to the quasi-initial masses, and the third group to smaller satellite drops. Bradley & Stow (1979) qualitatively describe a dependence in the position of the lower quasi-initial mass group as a function of B, which is consistent with our quantitative measurements (figure 7).…”
Section: Other Observablessupporting
confidence: 80%
“…Measurements for ∆ > 1 by List, MacNeil & McTaggart-Cowan (1970), McTaggart-Cowan & List (1975, and Bradley & Stow (1979) for water drops and by Arkhipov et al (1983) for water glycerine solutions, showed that, as in our case (e.g. compare figure 7e-h with figure 6 of List et al (1970) and figure 1 of Bradley & Stow 1979), the fragmentation of size-asymmetric systems is characterized by a three-peaked residue-mass distribution, two of the groups corresponding to the quasi-initial masses, and the third group to smaller satellite drops. Bradley & Stow (1979) qualitatively describe a dependence in the position of the lower quasi-initial mass group as a function of B, which is consistent with our quantitative measurements (figure 7).…”
Section: Other Observablessupporting
confidence: 80%
“…In this context, List et al [1970] studied neck breakup for the collision of class III drops with diameters ranging from 2.0 to 4.5 mm with velocity differences of the drop pairs equal to those observed in nature. They reported that 3 to 12 fragments (on average, 4.2) resulted from these interactions, the smaller number occurring when interacting drops maintain their original identity but loose mass to form a small satellite drop.…”
Section: Drop‐drop Interactionsmentioning
confidence: 99%
“…It occurred to List et al (1970) that collisions between larger drops, which usually result in the creation of several smaller "satellite" drops which are still large enough to allow rapid growth by accretion, may, when combined with the stochastic nature of the process which permits rapid growth of a few large drops, explain the observed precipitation growth times. However, a later study by Brazier-Smith et al (1973) showed that the effects on precipitation formation times are slight, although the process is important in altering the spectrum of drop sizes produced.…”
Section: The Discrete Nature Of the Accretion Processmentioning
confidence: 99%